An assessment of motivational activities of public elementary school pupils with attention deficit hyperactive disorder (adhd) in paranaque: basis for self-esteem enhancer program - Panganoron, Avegail R. (Manila : National University, 2014)
This study focuses on the assessment of motivational activities with attention deficit hyperactive disorder in public elementary school pupils in selected schools in Paranaque that will serve as basis for Self esteem Enhancer Program in decreasing maladaptive behaviors of children with attention problems.
Title Page -- Approval Sheet -- Acknowledgement -- Dedication -- Abstract -- Table of Contents -- Chapter 1: The Problem and its Setting -- Chapter 2: Review of Related Literature and Studies -- Chapter 3. Research Design and Methodology -- Chapter 4. Presentation, Analysis and Interpretation -- Chapter 5. Summary, Conclusions and Recommendations -- Bibliography -- Appendices -- Curriculum Vitae .
Research Method: Descriptive Design.
Includes bibliographical references.